Merriam-Webster's school dictionary. - Merriam-Webster, Inc. (Springfield, Mass. : Merriam-Webster, 1999)
A general dictionary for high school use, providing definitions, pronunciation, etymology, parts of speech designation, and other information.
"Especially for students ages 14-17"--T.p. verso.
Keywords: English language -- Dictionaries, Juvenile; Print books